Logic TK: algebric notions from Tarski's consequence operator - Feitosa, Hércules de Araujo [UNESP]; Nascimento, Mauri Cunha do [UNESP]; Grácio, Maria Cláudia Cabrini [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2010)
Tarski presented his definition of consequence operator to explain the most important notions which any logical consequence concept must contemplate. A Tarski space is a pair constituted by a nonempty set and a consequence operator. This structure characterizes an almost topological space. This paper presents an algebraic view of the Tarski spaces and introduces a modal propositional logic which has as a model exactly the closed sets of a Tarski space.

Tarski apresentou sua definição de operador de consequência com a intenção de expor as concepções fundamentais da consequência lógica. Um espaço de Tarski é um par ordenado determinado por um conjunto não vazio e um operador de consequência sobre este conjunto. Esta estrutura matemática caracteriza um espaço quase topológico. Este artigo mostra uma visão algébrica dos espaços de Tarski e introduz uma lógica proposicional modal que interpreta o seu operador modal nos conjuntos fechados de algum espaço de Tarski.
Keywords: Tarski space; Almost topological space; Consequence operator; Modal logic; Algebraic model; Espaço de Tarski; Espaço quase topológico; Operador de consequência; Lógica modal; Modelo algébrico